Imaging of osteoarthritis (OA): What is new?. Issue 4 (August 2016) - Mathiessen, Alexander; Cimmino, Marco Amedeo; Hammer, Hilde Berner; Haugen, Ida Kristin; Iagnocco, Annamaria; Conaghan, Philip G.
Abstract: In daily clinical practice, conventional radiography is still the most applied imaging technique to supplement clinical examination of patients with suspected osteoarthritis (OA); it may not always be needed for diagnosis. Modern imaging modalities can visualize multiple aspects of the joint, and depending on the diagnostic need, radiography may no longer be the modality of choice. Magnetic resonance imaging (MRI) provides a complete assessment of the joint and has a pivotal role in OA research. Computed tomography (CT) and nuclear medicine offer alternatives in research scenarios, while ultrasound can visualize bony and soft-tissue pathologies and is highly feasible in the clinic. In this chapter, we overview the recent literature on established and newer imaging modalities, summarizing their ability to detect and quantify the range of OA pathologies and determining how they may contribute to early OA diagnosis. This accurate imaging-based detection of pathologies will underpin true understanding of much needed structure-modifying therapies.